PENGETAHUAN IBU NIFAS TENTANG VITAMIN A DI PONKESDES DESA WONOSARI KECAMATAN NGORO KABUPATEN MOJOKERTO - Dyah Siwi Hety (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2016)
Vitamin A is an essential nutrient for humans, because these nutrients can not be made by the body, so it must be filled from the outside. Vitamin A may increase one of them on postpartum mother because at that time the mother at high risk for vitamin A deficiency.The purpose of this study was to know the level of knowledge about the postpartum mother vitamin A capsules in Wonosari Ponkesdes Ngoro Mojokerto. This study was descriptive. The study population was all postpartum mothers who are in the Ponkesdes Wonosari Ngoro Mojokerto. The sample used was total sampling throughout the postpartum mother (30 days post saline) in Ponkesdes Wonosari Ngoro Mojokerto. The collection of data is primary data and secondary data. The instrument used was a book cohorts of women and questionnaires closed (close ended) multiple choice. The results of this study can be seen that the level of know most mothers have knowledge good enough that 43% (13 people) of the total respondents, while the level of knowledge of postpartum mothers about vitamin A capsules at a level understand most of the women had less knowledge well that is 83% (25 people) of the total respondents.The results showed the level of knowledge about postpartum mothers vitamin A capsule in the region Ponkesdes Wonosari Ngoro Mojokerto majority of respondents are in the poor category. The right solution to tackle it then postpartum mothers in need of useful information about the capsule of vitamin A that is by improving education or socialization of vitamin A capsules to be easily understandable for women